Modbus Protocol as Gateway between different Fieldbus devices: a Didactic Approach - Cordeiro, Armando (2017)
Trabalho apresentado na 20th International Conference on Interactive Collaborative Learning, 27-29 setembro de 2017, Budapeste, Hungria